A Single-Center Retrospective Observational Study Evaluating the Favorable Predictive Factors for the Disease Control Time of Treatment with Tocilizumab in Patients of Rheumatoid Arthritis - Ishii N (Dove Medical Press, 2021)
Nobuyasu Ishii, Toshiki Shimizu, Yoshihisa Ishiura, Hideki Amuro, Tohru Nishizawa, Takeshi Tamaki, Shosaku Nomura First Department of Internal Medicine, Kansai Medical University, Moriguchi-City, Osaka, 570-8507, JapanCorrespondence: Toshiki ShimizuFirst Department of Internal Medicine, Kansai Medical University, 10-15 Fumizono-cho, Moriguchi-City, Osaka, 570-8507, JapanTel + 81-6-6992-1001Fax + 81-6-6992-1066Email shimizto@takii.kmu.ac.jpBackground: Tocilizumab (TCZ) is humanized monoclonal antibody against the interleukin-6 (IL-6) and receptor that has prominent efficacy for the treatment of rheumatoid arthritis (RA). We conducted a retrospective observational study to determine how long TCZ controls RA.Patients and Methods: We retrospectively reviewed the medical records of RA patients treated with TCZ. The aim of this study was to evaluate the contribution of clinical parameters to disease control time (DCT) in RA patients.Results: Overall, 144 patients were enrolled in the study. The median age of patients was 66 years (range: 34– 85 years). In univariate analysis, DCT was significantly increased in patients who had never received previous biologic disease-modifying anti-rheumatic drugs treatment (P = 0.0064). We also analyzed the contribution of the base line value of C-reactive protein (CRP) to DCT. We divided the patients with RA into two groups according to a cutoff value of 1.000 mg/dl. The median control times were 77.5 months (95% confidence interval [CI]: 44.8–not reached to median) and 34.5 months (95% CI: 17.0– 79.3) for patients with high and low CRP value, respectively. In univariate analysis, DCT was significantly increased in patients with a high CRP value (P = 0.0283). Multivariate analysis clearly revealed that a high baseline CRP value was an independent favorable predictive factor for longer DCT (hazard ratio, 0.608, 95% CI: 0.378– 0.981, P = 0.0416).Conclusion: These data clearly demonstrate that the baseline value of CRP was closely associated with long time DCT in patients of RA treated with TCZ.Keywords: rheumatoid arthritis, tocilizumab, C-reactive protein, platelet large cell ratio, disease control time